Impact of Group Art Therapy Using Traditional Chinese Materials on Self-Efficacy and Social Function for Individuals Diagnosed With Schizophrenia - Tong, Jie; Yu, Wei; Fan, Xiwang; Sun, Xirong; Zhang, Jie; Zhang, Jiechun; Zhang, Tingting (Frontiers in Psychology, 2021)
The purpose of this study was to examine the effect of group art therapy using traditional Chinese materials on improving the self-efficacy and social function of individuals diagnosed with schizophrenia. In China, little research has been conducted on patients to measure the effectiveness of group art therapy, especially using traditional Chinese materials. To address this research gap, 104 individuals diagnosed with schizophrenia were tested in a group art therapy program that included 30 treatment sessions and used a wide variety of materials, including traditional Chinese materials, such as Chinese calligraphy, traditional Chinese painting, Chinese embroidery, and Chinese beads. The effect of art therapy was analyzed using the General Self Efficacy Scale (GSES) and Scale of Social Skills for Psychiatric Inpatients (SSPI). This study demonstrates that group art therapy using traditional Chinese materials can improve self-efficacy and social function, reducing social and life function problems, and promote the recovery of individuals diagnosed with schizophrenia.